Condensed‐Phase, Halogen‐Bonded CF3I and C2F5I Adducts for Perfluoroalkylation Reactions1. Issue 12 (4th February 2015) - Sladojevich, Filippo; McNeill, Eric; Börgel, Jonas; Zheng, Shao‐Liang; Ritter, Tobias
Abstract A family of practical, liquid trifluoromethylation and pentafluoroethylation reagents is described. We show how halogen bonding can be used to obtain easily handled liquid reagents from gaseous CF3I and CF3CF2I. The synthetic utility of the new reagents is exemplified by a novel direct arene trifluoromethylation reaction as well as adaptations of other perfluoroalkylation reactions.